METODE KNN PADA SENTIMENT ANALISIS REVIEW PRODUK GAME ANDROID - Sucitra Sahara - Universitas BSI; Rizqi Agung Permana - STMIK Antar Bangsa (Indonesian Journal of Networking and Security (IJNS), 2022)
Abstract - Of the many comments that have been reviewed to obtain data set of positive and negative form of text that will be researchers for data classification by using the k-Nearest Neighbors (k-NN), k-NN is one of the most popular algorithms for pattern recognition. The rapid mushrooming android based application allows the vendor nor the parties competing businesses competing to create a variety of applications, ranging quality and high performance to quality is often questionable, so investigators held a screening of the application for android opinions or comments by people who have used the application and poured into the online media. Based on the data processing that has been done by comparing the Naive Bayes algorithm, Neural Network, Decision Tree and Machine Support Vector Machine using log data from students. Later in the tests to get the accuracy and AUC values of each algorithm so that the highest test results obtained by using support vector machine.